The Comparison Of Qingming Festival In Bengkalis City, Riau, And In Sungailiat, Bangka - Agustinus Sufianto; Nita Anggastia; Yanti Hayani (Bina Nusantara University, 2012)
Qingming Festival is a great festival and tradition for Chinese to commemorate their ancestors. This activity is considered necessary to do by Chinese nation. Qingming festival reflects xiaoxin (孝心) which means devotion toward the elderly or ancestor and is regarded as an educational culture. This tradition is well preserved until now. This study is objected to compare the Qingming festival held in Bengkalis City, Riau, and one held in Sungailiat, Bangka. By visiting directly those places and interviewing some Chinese people there, we will study and conclude some comparison on this subject.